Circulation of an Artemisinin-Resistant Malaria Lineage in a Traveler Returning from East Africa to France . (25th February 2022) - Coppée, Romain; Bailly, Justine; Sarrasin, Véronique; Vianou, Bertin; Zinsou, Boris Enock; Mazars, Edith; Georges, Hugues; Hamane, Samia; Lavergne, Rose Anne; Dannaoui, Eric; Balikagala, Betty; Fukuda, Naoyuki; et al.
Abstract: A returned traveler to Uganda presented with a Plasmodium falciparum kelch13 A675V mutant infection that exhibited delayed clearance under artesunate therapy. Parasites were genetically related to recently reported Ugandan artemisinin-resistant A675V parasites. Adequate malaria prevention measures and clinical and genotypic surveillance are important tools to avoid and track artemisinin resistance.